G563(P) What outcomes in neonatal research are important to healthcare workers and parents in nigeria?. (25th October 2020) - Read, S; Jibril, A; Tongo, K; Abimbola, A; Abdulkadir, I; Nabwera, H; Sinha, I; Allen, S
Abstract : Background: There is a scarcity of information around the most important outcomes for research in neonatal units in low-resource settings. Identification of important outcomes, which reflect shared clinical decisions between healthcare workers and parents, would inform the development of a core outcome set (COS) for use in research. Objective: To identify the outcomes that are important to healthcare workers and parents of newborn babies in neonatal units in Nigeria. Methods: A Delphi process was conducted amongst healthcare workers from various centres in Nigeria to identify and rank outcomes they considered important. Semi-structured interviews were then undertaken with parents of babies (mostly mothers) admitted to two neonatal units to ascertain their opinions and rank the outcomes previously identified by clinicians that were particularly important to them. Results: Outcome domains of most importance identified by healthcare workers and parents were short-term morbidity, nutrition, mortality, bonding, quality of life, length of hospital stay, financial cost, and long-term outcomes (both medical and functional). Healthcare workers prioritised short-term morbidity, neonatal mortality, and long-term complications; however, there was substantial variation between physicians and nurses, the latter raising quality of life as important. Parents placed more emphasis on quality of life and functional status than health complications. Conclusions: Clinical trials in low-resource settings should consider the outcomes identified in our study. The opinions of parents and nurses (as opposed to just physicians) need to be considered in developing COS for neonatal research in low-resource settings.